Association between Stigma and Pain in Patients with Temporomandibular Disorders. (21st September 2022) - Zhu, Rui; Zhang, Li; Zheng, Yun-Hao; Zhang, Zi-Han; Zhang, Li-Ming; Yang, Hao-Lun; Yue, Yuan; Xiong, Xin
Abstract : Objective . This study aims to explore the association between stigma and pain in patients with temporomandibular disorders (TMDs). Methods . Two hundred and twenty-five patients with TMDs were recruited, and they completed the questionnaires including the Visual Analogue Scale of Pain (VAS), Generalized Anxiety Disorder 7-Item (GAD-7), the Patient Health Questionnaire 9-item (PHQ-9), Jaw Functional Limitation Scale 8-item (JFLS-8), the Stigma Scale for Chronic Illness 8-item (SSCI-8), and other demographic and disease-related information. The total score of SSCI-8 indicated overall stigma, which could be classified into 2 subdomains, felt stigma and enacted stigma, according to their representative items, respectively. Then, the patients were divided into 2 groups in each subdomain of stigma according to their scores: stigma group (score ≥ 1) and no stigma group (score = 0). Results . Patients with overall stigma and enacted stigma presented significantly higher scores in VAS, GAD-7, PHQ-9, and JFLS-8 than those without overall stigma and those without enacted stigma, respectively. Significant differences between patients with and without felt stigma were only observed in GAD-7, PHQ-9, and JFLS-8. Patients with overall stigma and enacted stigma mainly suffered from pain-related TMDs (PTs) and combined TMDs (CTs). Overall stigma and enacted stigma rather than felt stigma were significantly associated with both PTs and CTs. Stigma, including overall stigma, enacted stigma, and felt stigma, was more associated with anxiety and depression and less related to jaw functional limitation of the patients with TMDs. Conclusion . Stigma, specifically enacted stigma, was correlated to pain in patients with TMDs. Stigma was more related to psychological problems than jaw functional limitation.